2003
DOI: 10.1128/jcm.41.5.2271.2003
|View full text |Cite
|
Sign up to set email alerts
|

Immunochromatographic Test for Rapid Detection of Streptococcus pneumoniae in the Nasopharynx

Abstract: Faden et al. recently reported the use of the NOW immunochromatographic test to rapidly detect nasopharyngeal colonization with Streptococcus pneumoniae (1). While the specificity of the test in this study was relatively high (97.7%), it is important to be aware that oropharyngeal colonizing bacteria other than S. pneumoniae may also produce positive results with this test. Specifically, Streptococcus mitis shares the antigen against which the NOW test is directed. This cross-reaction is recorded by the manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
0
10
1
Order By: Relevance
“…Also, pneumococcal antigen was detected for 30 days following initial subculture for all bottles. False-positive reactions may occur, and several authors have demonstrated that viridans group streptococci, in particular the Streptococcus mitis group, may cross-react with the pneumococcal C polysaccharide antigen (1,4,8,11). All three false-positive results in our study were due to organisms within the S. mitis group.…”
mentioning
confidence: 41%
“…Also, pneumococcal antigen was detected for 30 days following initial subculture for all bottles. False-positive reactions may occur, and several authors have demonstrated that viridans group streptococci, in particular the Streptococcus mitis group, may cross-react with the pneumococcal C polysaccharide antigen (1,4,8,11). All three false-positive results in our study were due to organisms within the S. mitis group.…”
mentioning
confidence: 41%
“…Although sharing many features in common with S. pneumoniae and S. mitis, S. pseudopneumoniae can be readily identified in a clinical laboratory by the combination of some simple phenotypic tests, particularly tests for optochin susceptibility and bile solubility. Interestingly, S. pseudopneumoniae, like S. mitis (8), produces a positive result with the NOW S. pneumoniae antigen test, indicating that the antigen is shared between the species. Unlike the findings previously reported by Arbique et al (1), who detected the pneumolysin gene in all of their S. pseudopneumoniae strains, five of our isolates tested negative for this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Testing for the presence of pneumococcal pneumonia with the CAD kit has been reported to exhibit longterm antigen-positive results regardless of antibiotic treatment (21,30). We therefore evaluated the effect of antibiotic treatment on RP-L7/L12 production in the mouse pneumonia model to determine whether this was a more sensitive and accurate readout of infection.…”
Section: Resultsmentioning
confidence: 99%